Cannabinoid-1 receptor neutral antagonist reduces binge-like alcohol consumption and alcohol-induced accumbal dopaminergic signaling. (15th March 2018) - Balla, Andrea; Dong, Bin; Shilpa, Borehalli M.; Vemuri, Kiran; Makriyannis, Alexandros; Pandey, Subhash C.; Sershen, Henry; Suckow, Raymond F.; Vinod, K. Yaragudri
Abstract: Binge alcohol (ethanol) drinking is associated with profound adverse effects on our health and society. Rimonabant (SR141716A), a CB1 receptor inverse agonist, was previously shown to be effective for nicotine cessation and obesity. However, studies using rimonabant were discontinued as it was associated with an increased risk of depression and anxiety. In the present study, we examined the pharmacokinetics and effects of AM4113, a novel CB1 receptor neutral antagonist on binge-like ethanol drinking in C57BL/6J mice using a two-bottle choice drinking-in-dark (DID) paradigm. The results indicated a slower elimination of AM4113 in the brain than in plasma. AM4113 suppressed ethanol consumption and preference without having significant effects on body weight, ambulatory activity, preference for tastants (saccharin and quinine) and ethanol metabolism. AM4113 pretreatment reduced ethanol-induced increase in dopamine release in nucleus accumbens. Collectively, these data suggest an important role of CB1 receptor-mediated regulation of binge-like ethanol consumption and mesolimbic dopaminergic signaling, and further points to the potential utility of CB1 neutral antagonists for the treatment of binge ethanol drinking. Highlights: A novel CB1 receptor neutral antagonist, AM4113 suppresses binge-like ethanol drinking. AM4113 reduces ethanol-induced increase in dopamine release in nucleus accumbens. AM4113 is rapidly absorbed and eliminated in plasma than in brain. AM4113 might be useful in the treatment of binge ethanol drinking.